How do New Zealand companies use capital investment post-completion audits for organisational learning? An exploratory study - Wilford-Denby, Darryl (Auckland University of Technology, 2014)
This exploratory research studies firstly the design setup of New Zealand’s publicly-listed companies for post-completion auditing (PCA). It secondly researches the prima facie occurrence of organisational learning (OL) within the same companies. Data was obtained from an online questionnaire and this study adopted a positivist stance, merely describing reality. The findings are similar to those in Finland by Huikku (2009). New Zealand companies, like their Finnish counterparts lack PCA system elements of organisational memory (OM). There is some evidence of prima facie single-loop learning consequent from PCA report recommendations. Post completion audits (PCAs) are intended to provide the ‘feedback loop’ in the capital investment decision-making process. This research aimed to discover the way(s) in which New Zealand companies use post-completion audits (PCAs) for organizational learning. Organizational learning (OL) is regarded as a primary reason for using PCAs and is important because companies can use it to improve future capital investment projects and processes. A survey was used to ascertain the uses of PCA in OL in NZX-listed public NZ companies. This study will add to the scant existing knowledge of how PCA information is used. From this study, the occurrence of double-loop learning was not clearly evident, with a major obstacle being the exclusion of policies and practices from the focus of PCA reporting. It is submitted that opportunities to research from this dissertation include the exclusion of policies and procedures from PCA which may preclude the potential for double-loop learning; the standardisation of PCA reporting as an accounting topic and the blatant absence of an organisational memory containing PCA reports and information from most companies.
Keywords: Post-completion auditing; Organisational learning; Public companies; Learning loops; Online questionnaire; Capital investment